2007
DOI: 10.1126/science.1137032
|View full text |Cite
|
Sign up to set email alerts
|

Response to Comment on "Coherent Control of Retinal Isomerization in Bacteriorhodopsin"

Abstract: Joffre attempts to show that the linear response of any quantum system to an external perturbation is phase insensitive, but he uses incorrect mathematical assumptions, misinterprets the time invariance principle, and ignores causality. We argue that the opposite case-an explicit phase dependence for a signal measured in the linear excitation regime-can equally be shown using Joffre's approach and assumptions.T he comment by Joffre (1) claims to make a general statement covering all possible cases of the field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 13 publications
1
53
1
Order By: Relevance
“…2 That proof deals with gas-phase photofragmentation of isolated molecules, with a focus on the long time limit at fixed energy in a degenerate continuum. However, a recent experiment on weak-field shapedpulse cis/trans isomerization of retinal, 3 as well as computational studies on model systems, 4 claims a demonstration of one-photon control of long-time isomerization yields by varying the relative phases of components of the incident radiation. In both cases, the system isomerization takes place within an open dissipative environment, where the earlier proof does not apply.…”
Section: Introductionmentioning
confidence: 99%
“…2 That proof deals with gas-phase photofragmentation of isolated molecules, with a focus on the long time limit at fixed energy in a degenerate continuum. However, a recent experiment on weak-field shapedpulse cis/trans isomerization of retinal, 3 as well as computational studies on model systems, 4 claims a demonstration of one-photon control of long-time isomerization yields by varying the relative phases of components of the incident radiation. In both cases, the system isomerization takes place within an open dissipative environment, where the earlier proof does not apply.…”
Section: Introductionmentioning
confidence: 99%
“…4 The retinal isomerization occurs within a few picoseconds of the photocycle initiation and changes the position of the Schiff base by ∼0.4 Å. 11,12 Even though this charge redistribution induces both an internal photovoltage within ns of illumination 13 and a significant change in the spectral properties of BR (λ max changes from 568 to 412 nm), 14 it results in a relatively minor conformational change (concentrated mainly in the orientation of helices F and G). 15 Here, the M163C mutation on the E-F loop of BR has been designed to exploit this sensitivity, that is to bring the most responsive part of the protein into close proximity to the underlying surface.…”
Section: ' Introductionmentioning
confidence: 99%
“…A seminal proof 3 showed that one-photon phase control was not possible for isolated molecular systems in which control is over products in the continuum. A subsequent experiment on control of retinal isomerization in bacteriorhodopsin 4 motivated controversy [5][6][7][8] and the need for clarification of conditions under which such control was possible. This clarification, provided in Ref.…”
Section: Introductionmentioning
confidence: 99%